PERFORMANCE OF LOWLAND RICE (ORYZA SATIVA L. VAR. NSIC RC216) FROM DIFFERENT SEED QUALITY PLANTING MATERIALS - Cagasan, Ulysses A; Cagasan, Christian Ulysses G (Journal of Agriculture and Technology Management; Vol 26 No 2 (2023): Vol 26 No 2 (2023): Journal of Agriculture and Technology Management (JATM) Volume 26 July - December 2023 Issue, 2023)
Seed quality is one of the critical considerations in crop production. However, most farmers did not observe the importance of rice quality and seed preparation as planting materials. This study aimed to determine the effects of seed quality (lighter and heavy seeds) on germination, growth, and yield performance of NSIC Rc216 as planting materials. The experiment was laid out in complete randomized design (CRD) with three replications. The treatments are as follows: T 1 –randomly taken from the seeds stock (check), T 2 - Floater/Light Seeds, and T 3 – Sinker/Heavy Seeds. Results revealed that heavy seeds significantly (p<0.05) gave higher % germination and vigor. However, heavy seeds were comparable to the control treatment (not tested for floatation) in terms of plant height (cm), fresh weight of seedling, number of productive tillers, days to maturity and percent germination, the weight of 1000 seeds g hill-1 and total grain yield tha -1 . However, lighter half-filled seeds showed a very inferior performance to the other treatments.